Larvicidal activity of the black pepper, Piper nigrum (Fam: Piperaceae) extracts on the cattle tick, Rhipicephalus australis (Acari: Ixodidae) - Marine Toussirot; Paul Coulerie; Thomas Hüe; Alexandre Maciuk; Valérie Kagy (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Background The cattle farming parasite Rhipicephalus australis is the main tick and one of the most important in the world from an economic point of view. Various studies have been developed in order to find plant extracts with effective acaricidal properties and environmentally friendly. Studies involving plant extracts for parasite control on commercial animal herds is a developing area in New Caledonia. Bioactive natural products play an important role as lead compounds in the development of new pesticides. Results The ethanolic extract of Piper nigrum L. dried fruits as well as the ethyl acetate extract and the methanolic extract of stems exhibited 100% larvicidal activity (50 mg/mL) against Rh. australis larvae, the cattle tick, an hematophagous parasite. Bioguided fractionation of the ethanolic extract of dried mature fruits using the same assay led to the isolation of five compounds belonging to piperamide family. The structures of isolated compounds were elucidated using spectroscopic methods: ESI-HRMS, 1H- and 13C-NMR spectral data, including DEPT and 2D-NMR experiments (COSY, HSQC, HMBC, and NOESY). These include 1 compound described for the first time in P. nigrum, homopellitorine (2) and 4 known compounds, namely pellitorine (1), pipyaqubine (3), 2-methylpropylamide (4), and N-isobutyl-2,4-eicosadienamide (5). Conclusion This first report on the larvicidal activity of P. nigrum extract and pure compounds on this tick species suggests that P. nigrum could be a natural biosourced alternative for the control of the larval stage of Rh. australis. Graphical Abstract